Implementation of Computer Course Program in Improving Digital Skills of Trainees at LKP Sulthan Computer Bondowoso - Aurelia, Zakinah; Imsiyah, Niswatul; Purnamawati, Frimha (Indonesian Journal of Adult and Community Education, 2024)
This research aims to describe the implementation of a computer course program in improving the digital skills of training participants at LKP Sulthan Computer Bondowoso. The technique for determining the location uses a purposive area and the technique for determining informants used is purposive sampling. The type of research used is descriptive research using a qualitative approach. The data collection methods used are observation, interviews and documentation methods. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Data validity checking techniques used include: extending participation, diligent observation and triangulation of sources and techniques. The results of the research can be concluded that the places and facilities at LKP Sulthan Computer include computers, theory rooms and practice rooms, presentation of material provided in accordance with Perpes SKKNI Number 08 Curriculum 2012, practice and assignments in the graphic design program, namely designing pamphlets and banners. The problem that often occurs in Sulthan's computer LKP is the difference in the comprehension abilities of training participants. At the end of the course program the instructor conducts a program closing reflection to review the training participants' abilities. The skills and creativity of the trainees can be seen from the way the trainees combine elements in graphic design and the trainees' communication skills can be seen when making presentations.